Analisis Peran Kepala Sekolah SDN 22 Kepahiang dalam Meningkatkan Mutu Pendidikan pada Tahun Ajaran 2019 – 2020 - Baka Imam Fathonah; Rossa Ayuni (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine: (1) how the roles and responsibilities of school principals in improving the quality of education; (2) what are the supporting and inhibiting factors of school principals in improving the quality of education. The results showed that: (1) as a leader in the school, the principal is responsible for all activities in the school, therefore, in improving the quality of education the principal has the following roles and responsibilities: including his role as educator, manager, administrator, supervisor, leader, innovator and motivator. (2) the supporting factors and inhibiting factors for school principals in improving the quality of education include, supporting factors: physical development that is starting to spread evenly. While the inhibiting factors for school principals in improving the quality of education are: the level of teacher discipline that is still lacking and the lack of facilities and infrastructure. In this study, researchers used qualitative research methods. Qualitative research is a research that prioritizes the process or quality of what is being studied. This method aims to understand social reality, namely seeing the world from what it is, not the world it should be, so a qualitative researcher must be an open minded person. Doing qualitative research properly means that you have a window to understand the world of psychology and social reality. In this study using 3 data collection techniques, namely: (1) Observation, is a data collection technique that emphasizes the direct experience of the researcher, observing himself, which is then recorded and recalled events and understanding complex situations. (2) Structured interview, is a systematic procedure for obtaining information about respondents in a condition where a set of questions are asked in the order prepared by the interviewer and the answers are recorded in a standardized form. (3) Documentation, is a record of events that have passed. Documents can be in the form of writing, pictures, monumental works of someone.